Economic Efficiency in Economic Analysis of Law - Famulski, Tomasz (Journal of Finance and Financial Law, 2017)
The aim of the article is to identify the category of economic efficiency on the grounds of L&E. According to the primary thesis of L&E economic efficiency is a fundamental legal value. The study discusses said thesis. On one hand, the controversy surrounding the thesis stem from lack of its unequivocal understanding. On the other, law has been functioning for centuries, while the question of its economic efficiency has only been raised for a few decades. Fundamental value, which has always been associated with law, is justice. It follows that the issue of various approaches to the relation between economic efficiency and justice in L&E is considered. Critical analysis of the literature allows to formulate arguments for and against each of these values in enacting and enforcing the law. Significant differences in various approaches to this matter are identified. Simultaneously, the assumption that efficiency is a value realized in the law beside justice is considered to be correct. The issue raised is important from the practical point of view. A theoretical consensus would support formulating a model, which would allow assessment of legal regulations based on criteria of economic efficiency and justice.